The Effect of Warm Ginger Compresses on Back Pain Intensity in Third Trimester Pregnant Women at the Jailolo Community Health Centre - Mahla Ahmad; Tut Rayani Aksohini Wijayanti (International Journal of Medicine and Health, 2025)
Back discomfort is a common musculoskeletal complaint among pregnant women, particularly in the third trimester, caused by biomechanical and physiological changes during pregnancy. This condition can interfere with daily activities, reduce sleep quality, and decrease overall comfort. Pharmacological treatments during pregnancy are limited due to safety concerns, making non-pharmacological therapies essential in primary healthcare. One alternative is the use of warm ginger compresses, which combine the benefits of heat therapy with the anti-inflammatory properties of ginger. This study aimed to examine the effect of warm ginger compresses on reducing back pain intensity in third-trimester pregnant women at the Jailolo Community Health Centre. The research used a pre-experimental one-group pretest–posttest design. The sample consisted of 16 pregnant women selected through purposive sampling. Pain intensity was measured using the Numeric Rating Scale (NRS) before and after the intervention. The treatment involved applying warm ginger compresses to the lower back following a standardized procedure. Data analysis was conducted using univariate and bivariate methods with the Wilcoxon signed-rank test. The results showed a significant reduction in back pain intensity after the intervention (p < 0.05). These findings indicate that warm ginger compresses are an effective, safe, and simple non-pharmacological method for reducing back pain in third-trimester pregnant women.